Predictive value of isolated very low QRS voltage in tilt-table test for neurally mediated syncope - Haichao Chen; Yiwei Cao; Lei Liang; Yan Gao; Jing Feng; Le Zhang; Lingxia Shi; Fengjun Chang; Gong Cheng; Haoyu Wu (SAGE Open Medicine, 2024)
Objective: The cause of syncope is generally determined based on clinical manifestations. There has been little discussion about the value of electrocardiograms for diagnosing neurally mediated syncope. The aim of this study was to test the predictive value of the isolated very low QRS voltage in tilt-table testing for suspected neurally mediated syncope in a Chinese population. Methods: This retrospective study enrolled patients with suspected neurally mediated syncope. Tilt-table testing was a part of the diagnostic examination. Each patient underwent echocardiography and electrocardiogram. isolated very low QRS voltage referred to a voltage of ⩽0.3 mV for the QRS complex in an isolated frontal lead or ⩽0.7 mV for the QRS complex in an isolated precordial lead. Results: In total, 157 patients were included in the tilt-table testing positive group, and 242 patients were included in the tilt-table testing negative group. Compared with the testing negative group, the testing positive group had more patients with isolated very low QRS voltage in the frontal leads ( p  < 0.001). Moreover, for patients with isolated very low QRS voltage in the precordial leads, no significant difference was noted between the testing positive group and testing negative group ( p  = 0.289). Isolated very low QRS voltage in the frontal leads demonstrated 84.08% sensitivity and 74.38% specificity for a positive tilt-table testing response. The area under the curve of isolated very low QRS voltage for a positive tilt-table testing response in frontal leads was 0.806 ( p  < 0.0001). Conclusion: In patients with suspected neurally mediated syncope, isolated very low QRS voltage in the frontal leads is a parameter that can predict a positive tilt-table testing response. The presence of isolated very low QRS voltage in frontal leads can serve as a parameter for evaluating syncope patients.